Effect of Ag Adatoms on High-Coverage Alkanethiolate Adsorption on Au(111) - Fonticelli, Mariano Hernán (2008)
Alkanethiol adsorption on Ag-adatom-modified Au(111) surfaces is studied by means of electrochemical techniques combined with Auger electron spectroscopy and periodic density functional (DF) calculations. The bimetallic surfaces are prepared by Ag underpotential deposition, and only the alkanethiolate high-coverage regime is considered. Alkanethiolate electrodesorption from Ag-modified Au(111) surfaces requires potentials shifted 0.3 eV in the negative direction with respect to the value corresponding to desorption from Au(111) surfaces. In agreement with this experimental result, DF calculations show that alkanethiolates prefer to be laterally adsorbed to Ag adatoms, the interaction energy being 0.3 eV larger than that corresponding to the same thiolate on Au(111). Therefore, it is concluded that alkanethiolates adsorbed on Au are likely to be observed only when the Ag adatom surface density is small enough or all Ag sites are occupied. The preference for alkanethiolate adsorption on adatoms is also found for a model surface containing Au adatoms on Au-(111). This indicates that no significant differences in electrodesorption potentials should be expected between Ag-adatom- and Au-adatom-rich surfaces. These findings and the analysis of experimental results strongly suggest that, under experimental conditions, the Au(111) surface does not exhibit a significant amount of Au adatoms, thus casting reasonable doubts on the adatom reconstruction models proposed for thiolates on Au-(111).